About Ahmad Hazini and his religious works (Journal of Oriental Studies, 2016)
The article discusses the importance of the work Ahmad Hazini in sufian ideas Khwaja Ahmad Yasawi.
Keywords: persian language; sufizm; Islamic culture; sufian tariqa; silsila.